(untitled) (Fiep Bulletin - online, 2013)
This text is a rehearsal from the experience of participating in Project Rondon edition 2008. The main objectives of this intervention were: providing activities that include an increased self-esteem of the residents of the city of Mostardas, as well as the implementation of actions relating to welfare and citizenship. To achieve this story we used the methods of "Observers Participation." As a result of this intervention we highlighted the unique contribution that an experience like this brings by participating in a project of this extension as it is able to provide a university level education, especially with regard to the learning community work.